2006
DOI: 10.1143/jjap.45.2827
|View full text |Cite
|
Sign up to set email alerts
|

Reference Signal Synthesized from a Cryogenic Sapphire Oscillator Improved by Power Control Servo

Abstract: Improvements in the frequency stability of a reference signal synthesized from a cryogenic sapphire oscillator (CSO) have been realized. This has been achieved by a power control servo with active Pound frequency stabilization in the loop oscillator based on a high Q-factor cryogenic sapphire resonator with a loaded Q-factor of 5 ×108 at 10.812 GHz and operating at a temperature of 6 K. The reference signal of 100 MHz was synthesized from the 10.812 GHz oscillation frequency. When compared with a 100 MHz hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…9) In a previous paper, we reported that the frequency stability of the CSO for averaging times shorter than 510 s could not be directly measured. 10) It was masked by shortterm fluctuations of the reference hydrogen maser. A second CSO (CSO2) now has been built to evaluate the first CSO (CSO1).…”
Section: Introductionmentioning
confidence: 99%
“…9) In a previous paper, we reported that the frequency stability of the CSO for averaging times shorter than 510 s could not be directly measured. 10) It was masked by shortterm fluctuations of the reference hydrogen maser. A second CSO (CSO2) now has been built to evaluate the first CSO (CSO1).…”
Section: Introductionmentioning
confidence: 99%
“…The technique we used to produce a 100 MHz signal from the 10.8 GHz frequency is described in detail elsewhere. 11) In this experiment, we used the divider stage of a divide-by-10 divider to down-convert 100 to 10 MHz. For the white noise source, we used a noise source (Agilent 346B) with an excess noise ratio of $15 dB, which corresponds to a noise temperature of $9171 K. Another output of the distributed amplifier can be used for the reference signal, if necessary, when calibrating a phase noise measurement system.…”
mentioning
confidence: 99%
“…Cryogenic sapphire oscillators (CSOs) [1][2][3][4] operating at microwave frequencies are capable of exhibiting a fractional frequency instability less than a part in 10 15 . Such oscillators are essential for operation of laser cooled atomic clocks at the quantum noise limit, 5 for precision tests of modern physics including the search for possible violations of Lorentz invariance, by comparing a CSO with a hydrogen-maser 6 or a CSO operating on the beat of same mode in a pair of resonators with orthogonal orientation, 7 and for searching for drift in the fine structure constants, which use fountain clocks with a CSO as the interrogation oscillator.…”
mentioning
confidence: 99%